Register in Reviewing Indonesian Food in Marina Tasha’s YouTube Vlog: Sociolinguistics Study - Salsabila Shafa Azzahra; Ervina CM Simatupang (Universitas Cokroaminoto Palopo, 2024)
This research, titled